Analysis of Gamification Implementation on Student Motivation and Learning Outcomes - Burhan, Rifa'atul Mahmudah; Jamilatul Badriyah (AI Society & STMIK Indonesia, 2025)
This study aims to analyze the effect of applying gamification methods on student motivation and learning outcomes in computer architecture and organization courses. The study was conducted using a quantitative approach with an experimental design to obtain valid data. Based on the research conducted, it can be concluded that the application of gamification methods has a significant positive impact on student motivation and understanding. Specifically, the use of gamification increased the average motivation score by 27.3, compared to an increase of 6.1 in conditions without gamification. Similarly, the aspect of understanding experienced an average increase of 27.1 with the application of gamification, while without gamification it only reached 5.4. In general, the results of this study indicate that the use of gamification in the learning process has a greater impact on increasing student motivation and understanding compared to conventional learning methods without gamification.